2022
DOI: 10.1080/1750984x.2022.2092884
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of heart rate variability in sport and exercise psychology

Abstract: Sport and Exercise Psychology (SEP) often adopts physiological markers in theory and practice, and one measure receiving increasing attention is heart rate variability (HRV). This paper aimed to provide a scoping review of the use of HRV within SEP. The protocol was made available on the Open Science Framework. Study inclusion criteria were examination of HRV in SEP, using athletes or healthy populations, peer-reviewed and published in English. Exclusion criteria were non-peer reviewed work, animal studies, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 223 publications
0
28
0
1
Order By: Relevance
“…In addition, there are limitations to measuring stress with HRV, and the relationships between subjective ratings and HRV are inconsistent and difficult to interpret, as are many of the numerous parameters that have been assessed with HRV. Nevertheless, studies of vagally mediated HRV are promising ( Mosley and Laborde, 2022 ), and could also be performed as part of future investigations on MPA management techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are limitations to measuring stress with HRV, and the relationships between subjective ratings and HRV are inconsistent and difficult to interpret, as are many of the numerous parameters that have been assessed with HRV. Nevertheless, studies of vagally mediated HRV are promising ( Mosley and Laborde, 2022 ), and could also be performed as part of future investigations on MPA management techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, several authors have included HR measurements in studies on for example stress during sports ( Oudejans and Pijpers, 2009 , 2010 ; Kusserow et al, 2010 ), repeated psychosocial stress induced by real and virtual stressors, including the same stressor over different periods of time ( Schommer et al, 2003 ; Kothgassner et al, 2021 , 2022 ), acute psychological stress ( Trotman et al, 2019 ) and MPA ( Yoshie et al, 2008 ; Yoshie et al, 2009 ; Kusserow et al, 2012 ; Kenny et al, 2013 ; Studer et al, 2014 ). In addition to HR, several authors have used heart rate variability (HRV) in the context of sports and exercise psychology to measure stress ( Mosley and Laborde, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with studies that found no changes in heart rate due to head‐out water immersion (Christie et al, 1990; Park et al, 1999). Moreover, its implementation appears particularly adequate in a large range of practical applications, such as sport (Al Haddad et al, 2010; Mosley & Laborde, 2022; Schnell et al, 2018), psychotherapy (Kyriakoulis et al, 2021), and medicine (Takahashi et al, 2020; Winter et al, 2018), in comparison to full‐body immersion. Regarding the effectiveness of such interventions for a given individual, it is important to note that the effects of the diving response on heart rate (and thus, potentially, cardiac vagal activity) vary among humans (Caspers et al, 2011; Lindholm & Lundgren, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As HR estimated at any given time represents the net effect of the neural output of the PNS, which slows HR and SNS, which accelerates HR, HRV also detects imbalance in the autonomous nervous system resulting from over or under stimulation of SNS and PNS. Therefore, the fluctuation in HRV values contains useful insights into many clinical applications, such as mental stress, exercise and rehabilitation, cardiovascular fitness, an indication of the pathological state, the progression of chronic disease, and even predicting the onset of diseases [46][47][48][49][50] . Depending on the application, HRV features are usually extracted from an ultra-short-term (< 5 minutes), short-term (around 5 minutes) or whole day 24 hours time frame 51 .…”
Section: Hrv Featuresmentioning
confidence: 99%